2014
DOI: 10.3390/ijms15069497
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Zosteric Acid for Mitigating Biofilm Formation of Pseudomonas putida Isolated from a Membrane Bioreactor System

Abstract: This study provides data to define an efficient biocide-free strategy based on zosteric acid to counteract biofilm formation on the membranes of submerged bioreactor system plants. 16S rRNA gene phylogenetic analysis showed that gammaproteobacteria was the prevalent taxa on fouled membranes of an Italian wastewater plant. Pseudomonas was the prevalent genus among the cultivable membrane-fouler bacteria and Pseudomonas putida was selected as the target microorganism to test the efficacy of the antifoulant. Zost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 60 publications
(85 reference statements)
1
15
0
Order By: Relevance
“…Obtained results are in line with previous data obtained with ZA and SA free in solution, suggesting that the molecules exert their anti‐biofilm activity even when immobilized on a surface . It is likely that both immobilized molecules may exploit their anti‐biofilm activity with a mode of action similar to that they have free in solution.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Obtained results are in line with previous data obtained with ZA and SA free in solution, suggesting that the molecules exert their anti‐biofilm activity even when immobilized on a surface . It is likely that both immobilized molecules may exploit their anti‐biofilm activity with a mode of action similar to that they have free in solution.…”
Section: Resultssupporting
confidence: 89%
“…Obtained results are in line with previous data obtained with ZA and SA free in solution, suggesting that the molecules exert their anti-biofilm activity even when immobilized on a surface. 17,19,[39][40][41] It is likely that both immobilized molecules may exploit their anti-biofilm activity with a mode of action similar to that they have free in solution. It has been found that ZA targets key step involved in E. coli biofilm formation by modulating the threshold level of the autoinducer-2 signal and inducing a hypermotile phenotype unable to firmly adhere on surfaces.…”
Section: Surface Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…Biofilms, complex surface-associated communities of microorganisms embedded in a self-produced polymeric matrix, are up to several orders of magnitude more resistant to antimicrobial agents than their planktonic counterpart (Villa et al 2010;Cappitelli et al 2014;Polo et al 2014). As a consequence, chemical treatment to prevent biological damage often involves considerable amounts of dangerous substances (Villa et al 2012b).…”
Section: Introductionmentioning
confidence: 99%